Design of asphalt mixtures integrating solid waste from the automotive industry (elastomer) and roadways (aged asphalt pavement) in Manabí, Ecuador - Navarrete Schettini, Gabriel Antonio (2019)
The purpose of this study is to design asphalt mixtures by integrating solid waste from used tires (elastomer) and aged asphalt pavement in Bolívar Canton, Manabí Province, Ecuador. The factors studied were 4%, 8%, 12% and 16% elastomer, and fine, average and coarse grading, using 52% aged asphalt pavement. A completely randomized two-way factorial arrangement, GxE+1, with thirteen treatments and three replications was used, where G corresponds to grading of aggregates used and E to elastomer. On the basis of the positive outcome of the design of asphalt mixtures with aged asphalt pavement, considering the addition of 4%, 8% and 12% of elastomer in the average and fine grading curves, it was concluded that the design can be used in light and medium traffic roads, such as those in Bolívar Canton, Ecuador.